Crosslinguistic Intelligibility of Russian and German Speech in Noisy Environment. (13th July 2017) - Potapova, Rodmonga; Grigorieva, Maria
Abstract : This paper discusses the results of the pilot experimental research dedicated to speech recognition and perception of the semantic content of the utterances in noisy environment. The experiment included perceptual-auditory analysis of words and phrases in Russian and German (in comparison) in the same noisy environment: various (pink and white) types of noise with various levels of signal-to-noise ratio. The statistical analysis showed that intelligibility and perception of the speech in noisy environment are influenced not only by noise type and its signal-to-noise ratio, but also by some linguistic and extralinguistic factors, such as the existing redundancy of a particular language at various levels of linguistic structure, changes in the acoustic characteristics of the speaker while switching from one language to another one, the level of speaker and listener's proficiency in a specific language, and acoustic characteristics of the speaker's voice.